O processo comunicativo no ensino aprendizado de crianças surdas: o caso da Escola Estadual Augusto Carneiro dos Santos - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The completion of work under the title "The communication process in the teaching-learning of deaf children: the case of State School Augusto Carneiro dos Santos" was due to the fact that deaf children need the means employed in visual literacy during the communication process in classroom. As a theoretical framework underlies the approaches of Vygotsky (2000, 2003), because it was, if not the first, but one of the precursors for the interest in deaf education; Fernandes (1990, 2003, 2010), an expert on the deaf; Guyton (2002 ), deals with the medical studies of humans as hearing, and Bordenave (1995), for understanding the functioning of the communicative process. For this research, we used the case study, with the aid of field research, as a technique, we used direct observation and semi-structured interview. Regarding the methodological approach we used qualitative, since the intention is to describe the facts observed and studied about how the visuals - including sign language. Thus, it was necessary to understand how communication processes are used for visual media in teaching and learning of deaf children and analyze these possible relationships in school. The data collected and systematized in this study had the aim of contributing to scientific knowledge regarding the importance of using the appropriate means of communication to succeed and concomitantly a teaching-learning for deaf children.
Keywords: Processo comunicativo; Ensino aprendizagem; Crianças surdas; Libras; Bilinguismo; Communicative process; Deaf children; Pounds; Bilingualism; Communication; CIÊNCIAS SOCIAIS APLICADAS: COMUNICAÇÃO